Effect of Pineapple Storage duration on the Quality of Bromelain age Duration of Pineapple on the Quality of the Bromelain Produced - Ririn Fatma Nanda; , Anwar Kasim (Journal of Global Innovations in Agricultural Sciences, 2025)
Pineapples are an abundant source of bromelain, however, during the distribution, the storage process can affect the bromelain content of pineapples, including rotting fruits. Those that have rotted are usually just thrown away without any further treatment. Therefore, this research was conducted to determine the effect of the distribution or storage time of pineapple on its bromelain content. Harvested pineapples are stored at room temperature for 9 days. Every three days, the pineapples were then sampled to see their bromelain content and profile. Crude enzyme yield, bromelain levels, crude enzyme activity are the main parameters in this research. From the research results, it can be observed that the longer the pineapple was stored, the greater the crude bromelain yield obtained. However, even though the yield was increasing, it was known that the levels of proteins and bromelain as well as the activity of the crude bromelain were actually getting smaller. The protein content of the crude bromelain decreased from 18.76 g/mL to 6.02 g/mL. Furthermore, the bromelain content also decreased from a content of 2.2435 mg/mL to 0.5175 mg/mL. Crude bromelain activity is directly proportional to bromelain levels, namely decreasing from 73.73 U/mg decreasing to 27.60 U/mg. It can be concluded from this research that the yield value is not directly proportional to the properties and levels of crude enzymes produced from pineapples that are stored for several days. Even though the pineapple had been stored for 9 days, the bromelain yield and activity obtained were still high. The results of this research showed that unsold pineapple and have started to rot can have its enzymes extracted as one of the steps that can be taken in processing pineapple products, and producers or farmers do not incur significant losses. Keywords: Bromeliaceae, waste management, enzyme activity, industrial practically, postharvest, proteolytic.